Estimation of average relative humidity in lower troposphere over Delhi using INSAT -cloud imageries during dry seasons (MAUSAM, 1988)
An attempt has been made in this paper to estimate average relative humidity in the lower troposphere using INSAT-IB cloud imagery received at Meteorological Data Utilization Centre (MDUC), New Delhi in this study three years (1984-86) INSAT-IB cloud data have been studied along with actual relative humidity data of Delhi. Based on statistical analysis of R.H. data and cloud classification regression equations have been developed to estimate average relative humidity value in the lower troposphere during January, April and October representing winter summer and post monsoon seasons when atmosphere IS In general  dry but becomes humid during active weather situations.